Biomechanical impact of cortical bone vs. traditional pedicle screw trajectories: a finite element study on lumbar spinal instrumentation - Li, Xishan; Abdel-Latif, Khaled H. A.; Schwab, Jefrem; Zhou, Xiang; Yang, Jie; Ritter, Zully M.; Schilling, Arndt F.; Reinhold, Maximilian (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundPedicle screw fixation using the cortical bone trajectory (CBT) enhances stability by engaging cortical bone, offering a valuable alternative to the traditional pedicle screw trajectory (TT). This study used finite element analysis to compare L4-5 instrumentation with CBT and TT screws, investigating whether the increased cortical bone engagement in CBT improves stability but makes it more susceptible to fatigue failure.MethodsA L3-sacrum model was generated using anonymized CT patient data, validated against existing studies, showing consistent ROM (range of motion) values. A mono-segmental L4-5 instrumentation with an interbody fusion cage was configured with both TT and CBT models, differentiated for healthy and osteoporotic bone (reduced Young’s modulus). Both models were exposed to simulated biomechanical loading conditions (compression, flexion, extension, lateral bending, and rotation) to calculate screw loosening and breakage risk. Screw loosening was assessed by measuring micro-movements within the screw hole, while screw breakage was evaluated based on maximum stress values and their frequency at the same locations.ResultsIn both healthy and osteoporotic bone, the CBT model exhibited smaller micro-movements compared to the TT model across all motions. For maximum stress in healthy bone, CBT showed lower stress during right rotation but higher stress in the other six motions. In osteoporotic bone, CBT stress exceeded TT stress in all conditions. The TT model in healthy bone showed stress concentrations at three locations, while CBT distributed stress across five sites. In osteoporotic bone, CBT showed stress at three locations, while TT distributed stress at four. Notably, in the TT model, maximum stress occurred at the screw head in six of seven movements, whereas in the CBT model, three movements showed maximum stress at the screw head and three at the screw tail.ConclusionCBT screws, by traversing three cortical layers, achieve greater integration with the vertebral bone compared to TT screws, thus reducing the risk of screw loosening. Although this increases the maximum stress on the screws, the stress is more evenly distributed, with the screw tail helping to reduce the risk of breakage.